ENGEMBANGAN VIRTUAL CLASS UNTUK PEMBELAJARAN AUGMENTED REALITY BERBASIS ANDROID - Rifiana Arief; Naeli Umniati (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
ABSTRACTAugmanted Reality for android handphone has been a trend among collage students of computer department who join New Media course. To develop this application, the knowladge about visual presentation theory and case study of Augmanted Reality on android phoneneed to be conducted. Learning media through virtual class can facilitate the students’ needs in learning and developing Augmanted Reality. The method of this study in developing virtual class for Augmented Reality learning were: a) having preparation to arrange learning unit, b) analyzing and developing the content of learning materials, c) designing storyboard or scenario of the virtual class, d) making website of virtual class, e) implementing the website as facility of online learning for Augmanted Reality. The available facilities in virtual class were to check learning units, to choose and download the material in the forms of e-book and presentation slides, to open the relevant website link for material enrichment as well as students’ practice with pre-test and post-test for measuring students’ understanding. By implementing virtual class for Augmanted Reality learning based Android, it is expected to provide alternative learning strategies for students that are interesting and easy to understand. The students are expected to be able to utilize this facility optimally in order to achieve the purposes of learning process and graduates’ competence. Keywords: VirtualClass, Augmented Reality (AR)